2018
DOI: 10.1097/gme.0000000000001065
|View full text |Cite
|
Sign up to set email alerts
|

What's in a name: are menopausal “hot flashes” a symptom of menopause or a manifestation of neurovascular dysregulation?

Abstract: Hot flashes have typically been classified as "symptoms of menopause" that should be tolerated or treated until they resolve. However, mounting evidence points to hot flashes as a manifestation of one or several underlying pathophysiological processes. Associations exist between the presence, timing of onset, severity, and duration of hot flashes, and the risk of several neurological (affecting sleep, mood, and cognition) and cardiovascular conditions. In addition, four consistent patterns of vasomotor disturb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 47 publications
1
9
0
3
Order By: Relevance
“…Despite this, mounting evidence supports that menopause symptom severity (especially VMS) is indicative of the clinical manifestation of one or several underlying pathophysiological processes [25]. Furthermore, hormone dysregulation during the menopause transition is thought to lead to a narrowing of the thermoneutral zone, resulting in increased VMS severity and thereby increased episodes of insomnia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, mounting evidence supports that menopause symptom severity (especially VMS) is indicative of the clinical manifestation of one or several underlying pathophysiological processes [25]. Furthermore, hormone dysregulation during the menopause transition is thought to lead to a narrowing of the thermoneutral zone, resulting in increased VMS severity and thereby increased episodes of insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, women who reported higher exercise frequency had modestly less severe menopause-related symptoms. Nonetheless, the reliance on subjective, selfreporting of VMS as a primary endpoint and the lack of valid, objective methods to assess VMS dynamics has limited research progress [25,29]. …”
Section: Discussionmentioning
confidence: 99%
“…Исследования, посвященные этому, немногочисленны, и данный вопрос требует дальнейшего изучения. Некоторые ученые предложили вместе с этим исследовать гены нейромедиаторных систем, таких как норадренергическая и серотонинергическая, поскольку через их пути осуществляются основные звенья патогенеза приливов жара [1].…”
Section: вазомоторные симптомы как индикаторы риска развития заболеваunclassified
“…В настоящее время ученые предлагают перестать рассматривать «приливы жара» лишь как симптом менопаузы, который легко можно купировать приемом эстрогенсодержащих препаратов или просто дождаться его окончания [1]. Вазомоторные симптомы должны быть признаны частью единого патофизиологического процесса, сопровождающего климактерий, проявлением нейроэндокринной и сосудистой дизрегуляции.…”
unclassified
“… 3 There is also a need to understand the underlying neurophysiological mechanisms in the climacteric syndrome, as many neuroendocrinal pathways seem involved in this process and considering it merely as an annoyance that needs to be handled for the time being may be a detrimental attitude. 6 Climacteric syndrome may be associated with deeper neurological disturbances which may have a bearing on future diseases. 6 …”
Section: Introductionmentioning
confidence: 99%